A Volatility and Persistence-Based Core Inflation - da Silva Filho, Tito Nicias Teixeira (IMF Working Papers; Working Paper ;, 2015)
Intuitively core inflation is understood as a measure of inflation where noisy price movements are avoided. This is typically achieved by either excluding or downplaying the importance of the most volatile items. However, some of those items show high persistence, and one certainly does not want to disregard persistent price changes. The non-equivalence between volatility and (the lack of) persistence implies that when one excludes volatile items relevant information is likely to be discarded. Therefore, we propose a new type of core inflation measure, one that takes simultaneously into account both volatility and persistence. The evidence shows that such measures far outperform those based on either volatility or persistence. The latter have been advocated in the literature in recent years.